2022
DOI: 10.1038/s41419-022-05144-6
|View full text |Cite
|
Sign up to set email alerts
|

The dual action of glioma-derived exosomes on neuronal activity: synchronization and disruption of synchrony

Abstract: Seizures represent a frequent symptom in gliomas and significantly impact patient morbidity and quality of life. Although the pathogenesis of tumor-related seizures is not fully understood, accumulating evidence indicates a key role of the peritumoral microenvironment. Brain cancer cells interact with neurons by forming synapses with them and by releasing exosomes, cytokines, and other small molecules. Strong interactions among neurons often lead to the synchronization of their activity. In this paper, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Exosomes released by glioma selectively enhance glutamatergic signal transduction by increasing the number of excitatory synapses in patients with brain cancer. 182 Due to the lack of research on tumor nerves, there is insufficient evidence to elucidate the communication effect of exosomes between tumors and neurons. It is important to explore this direction in the future.…”
Section: Potential Connections Between Exosomes and Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes released by glioma selectively enhance glutamatergic signal transduction by increasing the number of excitatory synapses in patients with brain cancer. 182 Due to the lack of research on tumor nerves, there is insufficient evidence to elucidate the communication effect of exosomes between tumors and neurons. It is important to explore this direction in the future.…”
Section: Potential Connections Between Exosomes and Neuronsmentioning
confidence: 99%
“…Recent studies have preliminarily confirmed this conjecture. Exosomes released by glioma selectively enhance glutamatergic signal transduction by increasing the number of excitatory synapses in patients with brain cancer 182 …”
Section: Exosomes Regulate the Communications Between Tme And Cancer ...mentioning
confidence: 99%
“…Furthermore, glioma cells are known to secrete exosomes that interact with the peritumoral environment, promoting proliferation, angiogenesis and immunosuppression [ 81 ]. Recently, it was found that these glioma-secreted exosomes also modify the electrical properties and cause de-synchronization of surrounding neurons [ 82 ]. Considering the massive cellular alterations found in cerebral tumors including LEATs, it is not strange to imagine profound changes in extracellular proteins that accompany the pathological intracellular protein synthesis.…”
Section: Changes In Extracellular Matrix In Tumors and Epilepsymentioning
confidence: 99%
“…GBM-derived EVs can regulate neuronal excitability [ 69 ] and miRs transfer (miR-148a and miR-9-5p) promotes angiogenesis in endothelial cells [ 70 , 71 , 72 , 73 ]. In bidirectional communication, brain endothelial cells release EVs containing tetraspanin CD9 to GBM [ 74 ], enhancing tumor progression through the inhibition of ubiquitination of IL6 receptor gp30 and promoting the activation of the signal transducer and activator of transcription 3 (STAT3) [ 75 , 76 , 77 , 78 ].…”
Section: Ev-mediated Communication Between Gbm and The Brain Tumor En...mentioning
confidence: 99%